Attitudes to antipsychotic drugs and their side effects: a comparison between general practitioners and the general population - Helbling, J; Ajdacic-Gross, V; Lauber, C; Weyermann, R; Burns, T; Rössler, W (BioMed Central, 2006)
Background: Attitudes towards antipsychotic medication play an important part in the treatment for schizophrenia and related disorders. We aimed measuring general practitioners' attitudes to antipsychotic drugs and their adverse side effects and comparing these with the attitudes of the general population. Methods: Analysis and comparison of two representative samples, one comprising 100 General Practitioners (GPs), the other 791 individuals randomly selected from the general population. The setting was the German speaking cantons of Switzerland. Results: General practitioners have significantly more positive attitudes towards anti-psychotic drugs than the general public. They reject widespread prejudices about the use of anti-psychotic medication significantly more than the general population. In particular the risk of dependency was assessed as 'low' by GP's (80%), in contrast to only 18% of the general population sample. In no instance did a majority of the GPs advise not tolerating any of the 10 possible adverse effects presented in this study. This is in marked contrast to the general population sample, where a majority recommended discontinuation for movement disorder (63%), strong tremor (59%), risk of dependency (55%) and feelings of unrest (54%). Conclusion: As well as effective management of side-effects being a vital aspect of patient and carer education, prescribing doctors need to be aware that their mentally ill patients are likely to be confronted with extremely negative public attitudes towards antipsychotic medication and with strong pressures to stop taking their medication in the event of side-effects.